Предмет: Математика,
автор: AbbySwait12
Упростите выражение
-4 * (1,5 с - 1) + 3*(с-5)
Ответы
Автор ответа:
0
-4*(1,5с-1)+3*(с-5)
ПОЛЬЗУЕМСЯ ПРАВИЛОМ:А*(В-С)=А*В-А*С ИЛИ А*(В+С)+А*В+А*С
ТЕПЕРЬ РЕШАЕМ:
-4*1,5с-4*(-1)+3*с-3*5=-6с+4+3с-15=-3с-11
__ _ __ __
_ __
2 МИНУСА=---+(правило)
1 чертой подчеркнуто Числа с переменной С
2 чертами подчеркнуто Числа
Теперь просто вычесляем
ПОЛЬЗУЕМСЯ ПРАВИЛОМ:А*(В-С)=А*В-А*С ИЛИ А*(В+С)+А*В+А*С
ТЕПЕРЬ РЕШАЕМ:
-4*1,5с-4*(-1)+3*с-3*5=-6с+4+3с-15=-3с-11
__ _ __ __
_ __
2 МИНУСА=---+(правило)
1 чертой подчеркнуто Числа с переменной С
2 чертами подчеркнуто Числа
Теперь просто вычесляем
Похожие вопросы
Предмет: Алгебра,
автор: wwickssl
Предмет: Литература,
автор: frezzyfox620
Предмет: Химия,
автор: Аноним
Предмет: Алгебра,
автор: DDariaV